HUBUNGAN INTERDEPENDENSI ANTARA MANAJEMEN LABA DENGAN INDEKS PENGUNGKAPAN SUKARELA - Novan Sakti Ardianto, 08.05.52.0122; Anggana, Greg (Students Journal of Accounting and Banking, 2012)
This study is a study that examined the relationship between earnings management relations with interdependence between voluntary disclosure index.The population in this study is a manufacturing company listed on the Stock Exchange in 2010. In this study, researchers used purposive sampling and obtained samples of some 93 companies.Results research get the value of p = 0.003 for the relationship between the index of disclosure of earnings management.. In contrast, earnings management conducted no significant effect on disclosure index (p value = 0.430).Keywords: Earnings management, Leverage, Stock Capitalization, Return, Net Profit, Voluntary DisclosureIndex